Geographic distribution and diversity of mitochondrial DNA haplotypes in South American sea lions (Otaria flavescens) and fur seals (Arctocephalus australis) - Tunez, Juan Ignacio (2007)
Genetic diversity and population structure of two species of South American pinnipeds, Otaria flavescens and Arctocephalus australis, from colonies located along the south-eastern coast of South America, were analysed using mitochondrial DNA haplotypes and compared with two populations of these species from the Pacific coast. A 445 base-pair segment, that included the tRNA-Glu gene (31 bp) and the adjacent cytochrome b gene (414 bp), was amplified using the polymerase chain reaction and sequenced directly. O. flavescens and A. australis showed six and seven haplotypes with 12 and 20 polymorphic sites, respectively. In the Atlantic Ocean there was an individual of A. australis that showed an haplotype that was highly divergent from the others. If this haplotype is excluded, the pattern of haplotype differentiation obtained for both species indicated a possible bottleneck that would have occurred 110,000 years ago, which also affected other pinnipeds. Colonies of the Atlantic and the Pacific did not share haplotypes. This result, based on a limited number of samples for the comparisons between oceans, suggests that populations from both oceans correspond to different evolutionarily significant units. O. flavescens on the Atlantic coast shows two clusters of breeding colonies in Uruguay and Patagonia, separated by a thousand kilometres. Colonies within clusters did not show significant differences in haplotype frequencies, but the difference between the clusters was significant, suggesting that they correspond to different conservation stocks.